Laboratory Evaluation of Tumor Biomarkers: An Updated Review - Moqbel, Arwa Ibrahem Saleh; Alsharari, Saad Musabbih Mutair; Alsharari, Tariq Mohammed Mubarak; Alsharari, Abdulrahman Kayid Samar; Alshrarai, Abdulrhman Ali Mathi; Hakami, Abdullah Mohammed Abdullah; Alrakkadi, Waleed Mater Abdulrahman (Journal of Ecohumanism, 2024)
Background: Tumor biomarkers are biochemical substances produced by cancer cells or other body cells in response to malignancies, released into circulation. They play a critical role in cancer diagnosis, treatment monitoring, and recurrence detection. Despite their clinical utility, tumor biomarkers have limitations, including limited specificity and sensitivity, necessitating their integration with other diagnostic modalities for accurate oncological assessment. Aim: This review aims to provide an updated overview of tumor biomarkers, their clinical applications, laboratory evaluation methods, and the challenges associated with their use in cancer management. Methods: The review discusses various laboratory techniques for tumor biomarker detection, including enzyme assays, immunoassays, high-performance liquid chromatography (HPLC), immunohistochemistry (IHC), fluorescent in situ hybridization (FISH), polymerase chain reaction (PCR), and microarray analysis. It also covers specimen requirements, preanalytical guidelines, and factors influencing biomarker levels, such as biological variability and analytical interferences. Results: Tumor biomarkers, such as alpha-fetoprotein (AFP), carcinoembryonic antigen (CEA), and prostate-specific antigen (PSA), are widely used in clinical practice. However, their diagnostic and prognostic value is optimized when combined with imaging and histopathological findings. Advances in proteomics and genomics have enhanced the identification and quantification of genetic and molecular biomarkers, improving cancer diagnosis and personalized treatment strategies. Conclusion: Tumor biomarkers are invaluable tools in oncology but are not standalone diagnostic modalities. Their clinical utility is maximized when integrated with other diagnostic approaches. Ongoing advancements in laboratory techniques and biomarker discovery hold promise for improving cancer detection, monitoring, and treatment outcomes.